Мікросателітний аналіз хромосом 6D та 7D інтрогресивних ліній пшениці, стійких до борошнистої роси - Штефюк, Т.В.; Антонюк, М.З. (Фактори експериментальної еволюції організмів, 2014)
Aims. Evaluation of polymorphism of wheat lines with introgressions from Aegilops species for microsatellite loci specific to 6D and 7D chromosomes. Methods. PCR of genome DNA with primer of specific SSR-loci. Results. The allelic polymorphism for SSR-loci of introgressive lines exceeds the limits, which determines by genotypes of parental genotypes. New alleles that are uncharacteristic to parental genotypes were reveal. Investigated loci have limited specifity to D genome. Conclusions. Polymorphism of SSR loci limits the potential of their use for investigation of introgressive lines genome structure. Microsatellites can be used for screening segregating populations taking into consideration the possibility of new allele appearance.